Simultaneous Quantification of Aspirin, Its Metabolite Salicylic Acid, and Salvianolic Acid B in Human Plasma Using UPLC-MS/MS - Weiyi Cao; Hezhi Yao; Zhenzhen Qian; Yi Wu; Shuge Wang; Rui Li; Rui Gao (International Journal of Analytical Chemistry)
Salvianolic acid B is the main active ingredient in salvianolate injection, which is produced by extracting danshen, the most commonly used Chinese herbal medicine for cardiovascular treatment. Clinically, salvianolate injection and aspirin are commonly combined to treat coronary heart diseases in patients with stable angina. To support clinical studies on drug-drug interactions (DDIs) between salvianolate injection and aspirin, a rapid and sensitive UPLC-MS/MS method for the simultaneous determination of aspirin (acetylsalicylic acid), its metabolite salicylic acid, and salvianolic acid B in human plasma was developed. The analytes and internal standard were extracted from the acidified plasma by liquid-liquid extraction with ethyl acetate and then separated by gradient elution with acetonitrile/0.5% formic acid in water on a C18 column. Salvianolic acid B, acetylsalicylic acid, and salicylic acid were quantified in multiple-reaction monitoring mode with negative ion electrospray ionization. The method was fully validated according to the current regulatory guidance for bioanalysis. Calibration curves in the range 5–6000 ng/mL, all with correlation coefficients greater than 0.99, were established using linear regression models for salvianolic acid B and acetylsalicylic acid and a quadratic model for salicylic acid. The validated method was successfully used to measure salvianolic acid B, acetylsalicylic acid, and salicylic acid concentrations in human plasma samples from 16 patients to observe the pharmacokinetic changes caused by DDIs.